The Analisis Kualitas Sumber Daya Manusia terhadap Pertumbuhan Ekonomi di Beberapa Wilayah Indonesia - Meyta Atna Susila (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
This study aims to determine whether the quality of human resources has an influence on economic growth in Indonesia. The quality of human resources owned by a country is important and should not be forgotten. Human resources are a key that drives all activities in a country. Therefore, to improve the quality of natural resources, support from the fields of education and health is needed which is a factor in improving the quality of human resources. The method carried out in this study is to use qualitative methods by observing and analyzing several existing and researched reading sources. This type of data is secondary data where the author takes the data that has been studied to be used as a reference to determine the influence of the quality of human resources on economic growth. From some of the data found, it shows a lot of results that reveal that factors from health and education in creating the quality of human resources affect economic growth in several regions in Indonesia.